Familial Ties, Location of Occupation, and Congregational Exit in Geographically-Based Congregations A Case Study of the Amish - Corcoran, Katie E.; Colyer, Corey; Kowalski, Brittany M. ca. 20./21. Jh.; Stein, Rachel E. (2021)
While many studies have examined the relationship between social ties and joining social movements and religious groups, few studies have investigated the relationship between social ties and the likelihood of exiting such groups. Additionally, research has not considered how geography affects the membership dynamics of geographically-based congregations, specifically whether factors associated with residential mobility may also affect congregational exit in geographically-based congregations.
Keywords: Amish; Congregations; Exit; Geography; Residential Mobility; Social Networks